Theorem analysis for application of fuzzy set in real life: - (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Fuzzy logic has its uses, but other new AI methods like machine learning and deep learningmay be better suited to tackling challenging, complex, and large data tasks. Once upon a time, it wasbelieved that the three most important AI programmes were the Genetic Algorithm, the Neural Network,and the Fuzzy Logic. While it's true that each of these methods has had its moment in the sun, it nowappears that the time has arrived for machine learning based on Neural Networks. Given that fuzzy logichas features like interpretability and universal approximation, the issue of whether or not it will play acrucial role in the current uptick in interest in artificial intelligence emerges. (AI). yes, but how exactly?When it comes to making choices, why doesn't automated technology make more use of impreciselogic?